2012
DOI: 10.1016/j.annepidem.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Management of Obesity in the National Health and Nutrition Examination Survey (NHANES), 2007–2008

Abstract: Although obesity is highly prevalent, only a small percentage of obese Americans are on anti-obesity medication. The withdrawal of sibutramine would have minimal impact on the general population. There is a need for more lifestyle changes in the majority of obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 26 publications
4
31
1
Order By: Relevance
“…Consistent with the present study using prescription data in a US primary care setting, data from two US national surveys have also indicated that the use of pharmacotherapy for weight loss among eligible patients is low 8, 9. In a retrospective cross‐sectional analysis of pharmacy data from the 2002–2007 US Medical Expenditure Panel Survey, only 0.61% of eligible patients used weight‐loss drugs 8.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with the present study using prescription data in a US primary care setting, data from two US national surveys have also indicated that the use of pharmacotherapy for weight loss among eligible patients is low 8, 9. In a retrospective cross‐sectional analysis of pharmacy data from the 2002–2007 US Medical Expenditure Panel Survey, only 0.61% of eligible patients used weight‐loss drugs 8.…”
Section: Discussionsupporting
confidence: 84%
“…8 Only 2% of American adults who are eligible for obesity pharmacotherapy actually receive them from a provider, even though nearly half of Americans meet the medical obesity pharmacotherapy criteria. 9,10 Numerous barriers preclude healthcare providers from adequately prescribing weight loss medications. First, inadequate training in medical schools and residency programs leads to a lack of confidence in prescribing such medications.…”
Section: Introductionmentioning
confidence: 99%
“…Scenario 1 (status quo) represented current rates of obesity and diet and exercise among the population (Table ). We assumed no AOM use under the status quo because less than 2% of individuals eligible for AOM receive such therapies . In scenario 2 (15% uptake), we assumed that 15% of eligible treatment‐naïve individuals initiated treatment with currently available AOM for chronic weight management (i.e., liraglutide 3.0 mg, lorcaserin, phentermine/topiramate, and naltrexone/bupropion) in each model cycle starting in 2019.…”
Section: Methodsmentioning
confidence: 99%